Are Books 'Inferior Goods' of Leisure Industry? - Sridhar, M. S. (Journal of Information and Knowledge, 1997)
Discusses the nature of leisure industry and composite commodity, explains four major determinants of demand analysis, namely, price, income of customers, prices of related commodities and tastes and preferences of customers, enumerates the concepts 'inferior', normal and luxury goods from the angle of income elasticity of demand, highlights the finding of western research that backs are inferior goods of leisure industry and concludes by stressing the need for recognition of books and libraries as part of leisure industry in the country and need for localised research about reading habits and use of libraries in the larger context of leisure industry.